Autonomous Modular Process Monitoring. (2016) - Denkena, Berend; Dahlmann, Dominik; Neff, Thomas
Abstract: Process monitoring is essential to detect process disturbances systematically in cutting machining processes. Hence, it can contribute significantly to process safety and thus to automatized production. Many different monitoring strategies have been developed and successfully tested. However, they usually require some manual parametrization effort by the machine operator and can be difficult to use. Furthermore, they usually focus on very specific process conditions. Therefore, an innovative modular autonomous monitoring system is being developed, which can monitor machining processes in single-item and series production and reduces parametrization effort for the operator to a minimum, thus, focusing on manageability of the system.